Congenital acneiform nevus with vellus hair hypertrichosis. - Mastrolonardo, M. (European Journal of Pediatric Dermatology, 2019)
A congenital segmental lesion directs towards the diagnosis of post-zygotic mutation nevus. The presence of whiteheads suggests follicular nevi. Among the latter we recall true hair follicle nevus, comedo nevus and acneiform nevus. The first is a small, congenital tumor of the face, the second is a linear lesion distributed according to the lines of Blaschko and the third, which is superimposable to the actual case, looks like a circumscribed skin patch with acne. In some cases of acneiform nevus (2) a mutation of the FGFR2 gene was showed in the affected skin. A germ-line mutation of the same gene is responsible for Apert’s syndrome, characterized by craniosynostosis and generalized severe acne. The presence of more evident vellus hairs, which highlights their relationship with acne, is singular in the actual case (1).